Epoxy pouring sealant and preparation method thereof

By using specific components and processes in epoxy potting glue, the problem of unbalanced curing speed and performance of traditional epoxy potting glue is solved, and the effects of high mechanical strength, excellent insulation performance and good moisture resistance are achieved.

CN119391345APending Publication Date: 2025-02-07JIANGXI OPT IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411667341.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Traditional epoxy potting adhesives are difficult to achieve the ideal balance of speed and performance during the curing process, and are prone to problems such as incomplete discharge of internal bubbles, brittle fracture, water absorption and insufficient weather resistance.

Method used

Using bisphenol A type epoxy resin, aliphatic amine curing agent, polyether type toughening agent, organic anhydride curing accelerator and nano-scale silica filler, the use of strict temperature control and vacuum defoaming technology is prepared with Large epoxy potting glue with excellent mechanical strength, insulation properties and moisture resistance.

Benefits of technology

It realizes rapid curing of epoxy potting adhesive, improves mechanical strength and insulation performance, enhances stability and reliability in harsh environments, and avoids brittle fracture and water absorption and expansion problems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses an epoxy pouring sealant and a preparation method thereof, and relates to the technical field of insulating materials. The epoxy resin composition comprises 50-75 parts of bisphenol A epoxy resin, the softening point of the epoxy resin is 80-90 DEG C, and the viscosity of the epoxy resin is 2000-10000 mPa.s at 25 DEG C; the curing agent is prepared by mixing hexamethylenediamine and diethylenetriamine according to a mass ratio of 1: 2; the flexibilizer comprises at least two polyether compounds with different molecular weights, and the molecular weights of the polyether compounds are respectively 1000Da and 3000Da; 1-3 parts of an organic anhydride curing accelerator, wherein the curing accelerator is formed by mixing phthalic anhydride and maleic anhydride according to the mass ratio of 1: 1; the average particle size of the filling agent is smaller than 50nm, and the surface of the filling agent is subjected to hydrophobization treatment. The epoxy pouring sealant has excellent insulating property, and is suitable for application scenarios with high requirements on electrical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of insulating materials, and in particular relates to an epoxy potting adhesive and a preparation method thereof. Background Art

[0002] Epoxy potting glue is mainly used for the packaging of electronic components. The purpose is to protect these components from external environmental factors (such as moisture, dust, chemicals, etc.), and also provide mechanical support and stability. With the development of electronic technology, electronic equipment is moving towards miniaturization, lightness, and high performance. This requires that the materials used for packaging must not only have good electrical insulation properties, but also have sufficient mechanical strength to withstand external shocks and vibrations. In certain specific applications, such as automotive electronics, aerospace, and other fields, electronic equipment also needs to work normally under extreme temperature changes, humidity changes, and other harsh environments.

[0003] During the curing process of traditional epoxy potting glue, it is difficult to achieve an ideal balance between curing speed and final performance. Too fast curing may cause internal bubbles to not be completely discharged, while too slow curing will extend the production cycle; although some epoxy resin potting materials have high mechanical strength, they are prone to brittle fracture when facing sudden external force impact; in an environment with high humidity, the material is easy to absorb water and swell, thus affecting its electrical performance. In addition, potting materials that are exposed to outdoor conditions for a long time also need to have good weather resistance.

[0004] To this end, we provide an epoxy potting adhesive and a preparation method thereof to solve the above-mentioned problems. Summary of the invention

[0005] In order to solve the above technical problems, the present invention is achieved through the following technical solutions:

[0006] The present invention is an epoxy potting adhesive and a preparation method thereof, comprising:

[0007] Component A: 50-75 parts of bisphenol A epoxy resin, the softening point of the epoxy resin is between 80-90°C, and the viscosity is 2000-10000 mPa·s at 25°C;

[0008] Component B: 20-30 parts of aliphatic amine curing agent, wherein the curing agent is a mixture of hexamethylenediamine and diethylenetriamine in a mass ratio of 1:2;

[0009] Component C: 5-10 parts of a polyether toughening agent, wherein the toughening agent comprises at least two polyether compounds with different molecular weights, the molecular weights of which are 1000Da and 3000Da respectively;

[0010] Component D: 1-3 parts of an organic anhydride curing accelerator, wherein the curing accelerator is a mixture of phthalic anhydride and maleic anhydride in a mass ratio of 1:1;

[0011] Component E: 5-10 parts of nano-scale silica filler, the average particle size of the filler is less than 50 nm, and the surface is hydrophobicized.

[0012] The present invention is further configured such that the volume resistivity of the epoxy potting adhesive after curing is greater than 1×10 15 Ω·cm, and the dielectric constant is less than 4.0.

[0013] The present invention is further configured that the toughening agent comprises at least one polyether compound containing a functional terminal group (such as a hydroxyl group or an amino group).

[0014] The present invention is further configured such that the hydrophobic treatment on the surface of the filler is performed using a silane coupling agent.

[0015] A method for preparing epoxy potting adhesive comprises the following steps:

[0016] Step a): Mix component A and component C in a high-speed stirrer at a stirring speed of 1000-2000 rpm for 10-20 minutes;

[0017] Step b): premixing component D and component E uniformly, and then adding them to the mixture obtained in step a), and adding a small amount of solvent to improve fluidity;

[0018] Step c): Add component B and continue stirring for 10-20 minutes under the same stirring conditions;

[0019] Step d): degassing the mixture under a vacuum degree of -0.09 MPa for 10-20 minutes;

[0020] Step e): pouring the degassed mixture into a mold, curing at 80-100° C. for 1-2 hours, and then performing secondary curing at 100-120° C. for 0.5-1 hour;

[0021] Step f): After curing is completed, demoulding is performed after cooling to room temperature.

[0022] The present invention is further configured such that the high-speed stirrer in step a) is a stirring device with a temperature control function, and the temperature is maintained at 25±2° C. during the stirring process.

[0023] The present invention is further configured that the solvent in step b) is anhydrous ethanol, and the amount added does not exceed 1% of the total weight.

[0024] The present invention is further configured such that the curing process in step e) is carried out in a pressure-controllable environment, preferably in a pressure range of 0.1-0.2 MPa.

[0025] The present invention has the following beneficial effects:

[0026] 1. The present invention selects bisphenol A epoxy resin with a softening point between 80-90°C and a viscosity of 2000-10000 mPa·s at 25°C as the base material, and combines it with aliphatic amine curing agent, so that the cured epoxy potting glue has good mechanical strength and is suitable for the packaging requirements of various electronic components; the addition of a polyether toughening agent, especially comprising at least one polyether compound containing a functional end group (such as a hydroxyl group or an amino group), makes the material show higher toughness when subjected to external force and is not prone to brittle fracture; the volume resistivity of the cured epoxy potting glue is greater than 1×10 15 Ω·cm, and the dielectric constant is lower than 4.0, which indicates that the material has excellent insulation properties and is suitable for application scenarios with high requirements for electrical properties, such as high-frequency circuits; the use of nano-scale silica filler and the hydrophobic treatment of its surface with silane coupling agent not only increase the hardness and wear resistance of the material, but also improve its stability and reliability in humid environments.

[0027] 2. The entire preparation process of the present invention adopts strict temperature control and vacuum degassing technology to ensure the consistency and high quality of the product. In particular, the staged curing method is adopted in the curing process, which can maintain the good performance of the material while avoiding the defects caused by the internal stress generated in the curing process; the curing agent formula of hexamethylenediamine and diethylenetriamine mixed in a mass ratio of 1:2, and the curing accelerator of phthalic anhydride and maleic anhydride mixed in a mass ratio of 1:1 can effectively adjust the curing speed, which not only ensures the demand for rapid curing, but also does not affect the performance of the final product.

[0028] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. DETAILED DESCRIPTION

[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] The present invention is an epoxy potting adhesive, comprising:

[0031] Component A: 50-75 parts of bisphenol A epoxy resin, the softening point of the epoxy resin is between 80-90°C, and the viscosity is 2000-10000 mPa·s at 25°C. The bisphenol A epoxy resin is used as a base material, and its softening point and viscosity ensure good fluidity and formability before curing, and provide the required mechanical strength and electrical properties after curing;

[0032] Component B: 20-30 parts of aliphatic amine curing agent, which is a mixture of hexamethylenediamine and diethylenetriamine in a mass ratio of 1:2. The aliphatic amine curing agent forms a cross-linked network by reacting with the epoxy resin to give the material the necessary physical properties. The specific ratio of hexamethylenediamine to diethylenetriamine optimizes the curing speed and final performance;

[0033] Component C: 5-10 parts of a polyether toughening agent, wherein the toughening agent comprises at least two polyether compounds with different molecular weights, the molecular weights being 1000Da and 3000Da respectively. The polyether toughening agent improves the impact resistance and elongation at break of the material, and the polyether compounds with different molecular weights can improve the elasticity and fluidity of the material;

[0034] Component D: 1-3 parts of an organic anhydride curing accelerator, wherein the curing accelerator is a mixture of phthalic anhydride and maleic anhydride in a mass ratio of 1:1. The organic anhydride curing accelerator accelerates the curing process. The mixture of phthalic anhydride and maleic anhydride can adjust the curing speed to meet different process requirements;

[0035] Component E: 5-10 parts of nano-scale silica filler, the average particle size of the filler is less than 50nm, and the surface is hydrophobicized. The nano-scale silica filler not only enhances the hardness and wear resistance of the material, but also improves the moisture resistance of the material after the hydrophobicization treatment.

[0036] Specifically, the volume resistivity of the epoxy potting adhesive after curing is greater than 1×10 15 Ω·cm, and the dielectric constant is lower than 4.0; the toughening agent contains at least one polyether compound containing a functional end group (such as a hydroxyl group or an amino group); the hydrophobic treatment of the filler surface adopts a silane coupling agent.

[0037] A method for preparing epoxy potting adhesive comprises the following steps:

[0038] Step a): Component A and component C are mixed evenly in a high-speed stirrer at a stirring speed of 1000-2000 rpm for 10-20 minutes to ensure that the toughening agent is evenly dispersed, thereby effectively improving the performance of the final product;

[0039] Step b): premixing component D and component E uniformly, and then adding them to the mixture obtained in step a), and adding a small amount of solvent to improve fluidity;

[0040] Step c): Add component B and continue stirring for 10-20 minutes under the same stirring conditions. The addition of component B starts the curing reaction, and the appropriate stirring time ensures the uniform distribution of the curing agent;

[0041] Step d): degassing the mixture at a vacuum degree of -0.09 MPa for 10-20 minutes. The vacuum degassing is to remove bubbles generated during the mixing process to prevent the formation of pores after curing, which affects the product performance;

[0042] Step e): pouring the degassed mixture into a mold, curing at 80-100° C. for 1-2 hours, and then performing secondary curing at 100-120° C. for 0.5-1 hour. The staged curing process ensures the completeness of the internal reaction of the material. Further high-temperature treatment after the initial curing can improve the crosslinking density and mechanical properties of the material.

[0043] Step f): After curing is completed, demoulding is performed after cooling to room temperature to prevent deformation caused by excessive temperature.

[0044] The high-speed stirrer in step a) is a stirring device with a temperature control function, and the temperature is maintained at 25±2° C. during the stirring process; the solvent in step b) is anhydrous ethanol, and the amount added does not exceed 1% of the total weight; the curing process in step e) is carried out in a pressure-controllable environment, and the preferred pressure range is 0.1-0.2 MPa.

[0045] The different proportions of ingredients or preparation conditions of the above epoxy potting glue were adjusted to obtain ten comparative products, and the performance of the obtained products was evaluated. The evaluation parameters were selected as curing time (min), volume resistivity (Ω·cm), impact resistance (kJ / m 2 ), elongation at break (%), hardness (Shore D), and wear resistance (mg / 1000 revolutions). The specific parameters of the ten comparison products are adjusted as follows:

[0046] Comparative product 1: Increase the proportion of component A (bisphenol A epoxy resin) to 75 parts;

[0047] Comparative product 2: Reduce the proportion of component B (aliphatic amine curing agent) to 20 parts;

[0048] Comparative product 3: Increase the proportion of component C (polyether toughening agent) to 10 parts;

[0049] Comparative product 4: Reduce the proportion of component D (organic acid anhydride curing accelerator) to 1 part;

[0050] Comparative product 5: increasing the proportion of component E (nano-silica filler) to 10 parts; Comparative product 6: changing the stirring speed in step a) to 2000 rpm;

[0051] Comparative product 7: Changing the amount of solvent in step b) to 2% of the total weight;

[0052] Comparative product 8: Changing the stirring time in step c) to 30 minutes;

[0053] Comparative product 9: changing the vacuum degree in step d) to -0.08 MPa;

[0054] Comparative product 10: Change the curing temperature in step e) to 120°C and the curing time to 2 hours. The evaluation parameter data table of the corresponding product is as follows:

[0055]

[0056]

[0057] Combining the above data results, we can know that the relationship between product performance and related parameters is:

[0058] Relationship between curing time and curing agent ratio: When the curing agent ratio in comparative product 2 was reduced to 20%, the curing time increased to 70 minutes, which indicates that a lower curing agent ratio will lead to a slower curing speed; when the curing agent ratio in comparative product 4 remained unchanged, the curing time increased to 75 minutes, which may be due to other factors (such as toughening agent or filler ratio) affecting the curing speed;

[0059] The relationship between viscosity and resin ratio: For comparison product 1, the ratio of bisphenol A epoxy resin is increased to 75 parts, and the viscosity increases from 6000mPa·s to 7000mPa·s, which shows that the increase in resin ratio will increase the viscosity of the material and affect its fluidity; for comparison product 5, the ratio of bisphenol A epoxy resin is further increased to 75 parts, and the viscosity increases to 7500mPa·s. The performance after curing is improved, but it may affect the processing difficulty.

[0060] Relationship between impact resistance and toughening agent ratio: Compared with product 3, increasing the proportion of polyether toughening agent to 10 parts, the impact resistance increases from 2.5kJ / m 2 Increased to 2.8 kJ / m 2 This shows that the increase in the proportion of toughening agent significantly improves the impact resistance of the material; in comparison with product 7, although the proportion of toughening agent remains unchanged, the curing time increases and the impact resistance drops to 2.3 kJ / m 2 , which indicates that the curing time also has an effect on the impact resistance of the material.

[0061] The relationship between the elongation at break and the type of toughening agent: For comparative product three, the proportion of toughening agent was increased, and the elongation at break increased from 150% to 160%, which shows that the addition of toughening agent can improve the flexibility of the material; for comparative product ten, although the proportion of toughening agent remained unchanged, the adjustment of curing temperature and time made the elongation at break reach 162%, which shows that suitable curing conditions can also improve the elongation at break of the material.

[0062] The relationship between hardness and filler ratio: For comparison product 5, the ratio of nano-silica filler was increased to 10 parts, and the hardness decreased from 75ShoreD to 70ShoreD, which shows that although the increase of filler increases the hardness, it may affect the softness of the material; for comparison product 9, although the filler ratio remains unchanged, the adjustment of curing conditions makes the hardness return to 75ShoreD, which shows that the curing conditions also have a great influence on the hardness of the material.

[0063] Relationship between wear resistance and curing conditions: For comparative product three, the filler ratio was increased, and the wear resistance decreased from 15mg / 1000 revolutions to 13mg / 1000 revolutions, which shows that the increase of fillers can improve the wear resistance of the material; for comparative product seven, although the filler ratio remained unchanged, the adjustment of curing conditions increased the wear resistance to 15.8mg / 1000 revolutions, which shows that curing conditions also have an important influence on wear resistance.

[0064] In summary, the curing agent ratio should be kept within an appropriate range (such as 25-30 parts) to ensure a reasonable curing speed.

[0065] Adjust the resin ratio according to application requirements. If higher mechanical strength is required, the resin ratio can be appropriately increased; if better fluidity is required, the resin ratio should be reduced.

[0066] The proportion of toughening agent can be appropriately increased (e.g., 5-10 parts) to improve the impact resistance and elongation at break of the material.

[0067] Increase the filler ratio appropriately (e.g. 5-10 parts) to improve the hardness and wear resistance of the material, but be careful not to increase it excessively so as not to affect the flexibility of the material.

[0068] Select appropriate curing temperature and time to achieve the best comprehensive properties; for example, higher curing temperature and longer curing time help to improve the crosslinking density and mechanical properties of the material.

[0069] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0070] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. An epoxy potting adhesive, characterized in that: include: Component A: 50-75 parts of bisphenol A epoxy resin, the softening point of the epoxy resin is between 80-90°C, and the viscosity is 2000-10000 mPa·s at 25°C; Component B: 20-30 parts of aliphatic amine curing agent, wherein the curing agent is a mixture of hexamethylenediamine and diethylenetriamine in a mass ratio of 1:2; Component C: 5-10 parts of a polyether toughening agent, wherein the toughening agent comprises at least two polyether compounds with different molecular weights, the molecular weights of which are 1000Da and 3000Da respectively; Component D: 1-3 parts of an organic anhydride curing accelerator, wherein the curing accelerator is a mixture of phthalic anhydride and maleic anhydride in a mass ratio of 1:1; Component E: 5-10 parts of nano-scale silica filler, the average particle size of the filler is less than 50 nm, and the surface is hydrophobicized.

2. The epoxy potting adhesive according to claim 1, characterized in that: The volume resistivity of the epoxy potting adhesive after curing is greater than 1×10 15 Ω·cm, and the dielectric constant is less than 4.

0.

3. The epoxy potting adhesive according to claim 1, characterized in that: The toughening agent comprises at least one polyether compound containing a functional terminal group (such as a hydroxyl group or an amino group).

4. The epoxy potting adhesive according to claim 1, characterized in that: The hydrophobic treatment on the surface of the filler adopts a silane coupling agent.

5. The method for preparing the epoxy potting adhesive according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step a): Mix component A and component C in a high-speed stirrer at a stirring speed of 1000-2000 rpm for 10-20 minutes; Step b): premixing component D and component E uniformly, and then adding them to the mixture obtained in step a), and adding a small amount of solvent to improve fluidity; Step c): Add component B and continue stirring for 10-20 minutes under the same stirring conditions; Step d): degassing the mixture under a vacuum degree of -0.09 MPa for 10-20 minutes; Step e): pouring the degassed mixture into a mold, curing at 80-100° C. for 1-2 hours, and then performing secondary curing at 100-120° C. for 0.5-1 hour; Step f): After curing is completed, demoulding is performed after cooling to room temperature.

6. The epoxy potting adhesive and preparation method thereof according to claim 5, characterized in that: The high-speed stirrer in step a) is a stirring device with a temperature control function, and the temperature is maintained at 25±2°C during the stirring process.

7. The epoxy potting adhesive and preparation method thereof according to claim 5, characterized in that: The solvent in step b) is anhydrous ethanol, and the amount added does not exceed 1% of the total weight.

8. The epoxy potting adhesive and preparation method thereof according to claim 1, characterized in that: The curing process in step e) is carried out in a pressure-controlled environment, preferably in the pressure range of 0.1-0.2 MPa.